PENERAPAN MODEL ANALISA PERATURAN PERUNDANG-UNDANGAN (MAPP) DI SEKTOR PERTAMBANGAN PASCA DIKELUARKANNYA UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAH DAERAH DALAM RANGKA OTONOMI DAERAH (Lex Jurnalica, 2021)
ABSTRACTThe management of natural resources in Indonesia must realize the greatest prosperity of the people as stated in the provisions of Article 33 paragraph 3 of the 1945 Constitution of the Unitary State of the Republic of Indonesia, therefore the management of natural resources, especially the mining sector, must reflect the ideals of the country. Since the issuance of Law Number 22 of 1999 concerning Regional Government, the State has implemented a system of regional autonomy or decentralization widely with the aim of providing opportunities and equal distribution of welfare to remote areas of the country, so that at that time regions were given the freedom to regulate their regions and obtain rights. - welfare rights including to manage natural resources. Thus, since Law Number 22 of 1999 which was later replaced by Law 32 of 2004 concerning Regional Government, Regional Governments have been given the authority to manage natural resources, including the mining sector. The mining sector in areas that have mining potential such as minerals and coal, or Oil and Gas, is one of the supporting factors for the economy and regional income, as well as providing job opportunities for local residents. Local governments are given the authority to grant mining permits and supervise the mining sector, both in provincial and district areas. In Government Regulation Number 38 of 2007, the Regency Government has the authority to grant mining permits to mining entrepreneurs who wish to open a Mineral and Coal mining business in certain regencies, however, since the issuance of Law Number 23 of 2014 as a substitute for Law Number 32 In 2004 concerning Regional Government, the authority of the Regency Government to grant Mineral and Coal Mining Permits was taken over by the Provincial Government, this is what needs to be further studied, considering that many mining businesses are actually located in Regency administrative areas, so it is also necessary to see the welfare impact obtained by the district as a result of the enactment of Law Number 23 of 2014. On the other hand, Law Number 4 of 2009 concerning Minerals and Coal (Minerba) still provides an administrative function to grant permits for the Head of the Regency, as well as its supervisory function, so that there is an indication of disharmony between the Minerba Law and the Regional Government Law. For that, researchers will use the Legislative Regulations Impact Analysis Model (MAPP) to see the consequences of this disharmony.Keywords: Regional Autonomy, Distribution of Central and Regional Government Authorities, Disharmony, Impact of Disharmony ABSTRAKPengelolaan sumber daya alam di Indonesia harus mewujudkan sebesar-besarnya kemakmuran rakyat sebagaimana dinyatakan dalam ketentuan Pasal 33 ayat 3 Undang-undang Dasar Negara Kesatuan Republik Indonesia 1945 , oleh krena itu pengelolaan sumber daya alam khususnya sektor pertambangan harus mencerminkan cita negara tersebut. Sejak dikeluarkannya Undang-undang Nomor 22 tahun 1999 tentang Pemerintah Daerah, Negara telah memberlakukan sistem otonomi daerah atau desentralisasi secara luas dengan tujuan untuk memberi kesempatan dan pemerataan kesejahteraan hingga pelosok-pelosok negeri, sehingga pada waktu itu daerah diberi keleluasaan untuk mengatur daerahnya serta mendapatkan hak-hak kesejahteraan termasuk untuk mengelola sumber daya alam. Dengan demikian, sejak Undang-undang Nomor 22 tahun 1999 yang kemudian diganti dengan Undang-undang 32 tahun 2004 tentang Pemerintah Daerah, Pemerintah Daerah diberi kewenangan untuk mengurus sumber daya alam, termasuk sektor pertambangan. Sektor Pertambangan di daerah yang memiliki potensi tambang seperti mineral dan batubara, atau Minyak dan Gas Bumi, menjadi salah satu penunjang perekonomian dan pendapatan Daerah, disamping memberikan kesempatan lapangan kerja bagi penduduk daerah setempat. Pemerintah Daerah diberi kewenangan untuk memberikan ijin pertambangan dan pengawasan sektor tambang, baik di wilayah propinsi maupun kabupaten. Dalam Peraturan Pemerintah Nomor 38 tahun 2007  , Pemerintah Kabupaten berwnang memberi perizinan tambang kepada pengusaha tambang yang ingin membuka usaha tambang Mineral dan Batu Baradi wilayah kabupaten tertentu, Akan tetapi, sejak dikeluarkannya Undang-undang Nomor 23 tahun 2014 sebagai pengganti Undang-undang Nomor 32 tahun 2004 tentang Pemerintah Daerah , kewenangan Pemerintah Kabupaten memberi Izin Pertambangan Mineral dan Batubara diambil alih oleh Pemerintah Daerah Propinis, hal inilah yang perlu dikaji lebih lanjut, mengingat banyak usaha pertambangan yang justru berada di wilayah-wilayah administrative Kabupaten, demikian juga perlu dilihat dampak kesejahteraan yang diperoleh kabupaten akibat pemberlakuan UU Nomor 23 tahun 2014 tersebut. Di sisi lain, Undang-undang Nomor 4 Tahun 2009  Tentang Mineral dan Batubara  (Minerba) masih memberikan fungsi administrative untuk memberi izin adalah Kepala Daerah Kabupaten, demikian juga dengan fungsi pengawasannya, sehingga terdapat indikasi disharmoni antara UU Minerba dengan UU Pemerintah Daerah. Untuk itu, peneliti akan menggunakan Model Analisa Dampak Peraturan Perundang-undangan (MAPP) untuk melihat akibat dari disharmoni tersebut.Kata Kunci: Otonomi Daerah, Pembagian Kewenangan Pemerintah Pusat dan Daerah, Disharmoni, Dampak Disharmoni